Variability of whole and peak match physical performance in highly trained female academy soccer players: A multi-club analysis - Naomi Myhill; Dan Weaving; Nick Dalton Barron; Andy Hudson; Steve Barrett; Stacey Emmonds (PLoS ONE, 2025)
Objective Quantify between-match, -player and -team variability and compare whole- and peak-match locomotor characteristics between positions in elite female academy soccer. Method Foot-mounted inertial measurement unit data were collected from 11 Women’s Super League Academy teams (n = 257 players; 171 matches). Differences between positions and variability were analysed using partial least squares correlation analysis (PLSCA) and linear mixed effects. Two latent variables were computed as composite scores of either whole match or peak intensity variables from the PLSCA. Results Between-match variability of whole- and peak-match locomotor characteristics were similar (2 to 24% vs 0.2 to 22%). Between-team and -player variability was higher for whole- than peak-match locomotor characteristics (1 to 20% vs 0.1 to 3%, 8 to 112% vs 0.3 to 77%). From 30 pairwise comparisons, there were two large effect size (ES) differences (p < 0.001), WM had greater whole and peak match composite intensity than CDM. There were 10 moderate ES differences (p < 0.05), with WM greater than CD and CAM, F greater than CD and CDM and WD greater than CDM. All other comparisons were non-significant, trivial or small. Conclusion Whole- and peak- match locomotor characteristics are similar across all outfield positions in elite female academy soccer. Between-match variability was greater for sprint distance than all other locomotor characteristics. Low variability between teams for peak locomotor characteristics means practitioners can be confident using peak reference values from this study and use them to evaluate training drill intensities of tactical-technical drills.